Factors associated with myopia in Korean children: Korea National Health and nutrition examination survey 2016–2017 (KNHANES VII) - Hyuna Kim; Jin Seok Seo; Woong-Sun Yoo; Gyu-Nam Kim; Rock Bum Kim; Jae Eun Chae; Inyoung Chung; Seong-Wook Seo; Seong Jae Kim (BMC Ophthalmology, 2020)
Abstract Background To evaluate the prevalence and risk factors associated with myopia and high myopia in children in South Korea. Methods A total of 983 children 5–18 years of age who participated in the Korean National Health and Nutrition Examination Survey 2016–2017 (KNHANES VII), a nationwide population-based cross-sectional study, were evaluated. Myopia and high myopia were defined as a spherical equivalent (SE) ≤ − 0.5 diopters (D) and SE ≤ --6.0 D. The association between refractive errors and potential risk factors for myopia was analyzed. Results The prevalence of myopia and high myopia was 65.4 and 6.9%, respectively. Older age and parental myopia were significantly associated with both myopia and high myopia, while higher body mass index (BMI) was associated with high myopia only. Although the proportion of subjects who spent more time on near work activities (≥4 h/day) was sequentially increased with increased refractive error, this tendency was not statistically significant by multivariable logistic regression. Conclusions Korean children had a high prevalence of myopia and high myopia. In this age group, the risk of myopia increased with aging and parental myopia. Higher BMI may be associated with high myopia.